1996
DOI: 10.1080/09712119.1996.9706143
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Age and Egg Production, Egg Components and Lipoprotein, Lipids and Fatty Acids of the Plasma and Eggs of Laying Hens

Abstract: Shafey, T.M. 1996. The relationship between age and egg production, egg components and lipoprotein, lipids and fatty acids of the plasma and eggs of laying hens. J. Appl. Anim. Res., 10:The relationship was studied between the age of hens from 27 to 51 weeks and production, size and components of their eggs, the lipid and fatty acid content of the yolks and the lipid composition of very low density lipoproteins (VLDL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…Additionally, hatchability traits were not influenced by age of the hen. These observations were in agreement with Shafey (1996), Peebles et al (2000), Silversides & Scott (2001), Oloyo (2003), Van den Brand et al (2004), Rizzi & Chiericato (2005), Johnston & Gous (2007) who showed that the egg weight increased with the hens' age. Abiola (1999) observed a positive correlation between egg size and chick hatching weight.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, hatchability traits were not influenced by age of the hen. These observations were in agreement with Shafey (1996), Peebles et al (2000), Silversides & Scott (2001), Oloyo (2003), Van den Brand et al (2004), Rizzi & Chiericato (2005), Johnston & Gous (2007) who showed that the egg weight increased with the hens' age. Abiola (1999) observed a positive correlation between egg size and chick hatching weight.…”
Section: Discussionsupporting
confidence: 81%
“…Genetic differences in egg yolk cholesterol content between S1 and S2 birds were related to differences in egg yolk weight and rate of lay rather than to egg yolk cholesterol concentration or daily egg yolk cholesterol output. A positive relationship between yolk weight and yolk cholesterol content has been reported by Shafey (1996). However, these results were not in agreement with Nichols et al (1963), who reported an inverse relationship between yolk weight and yolk cholesterol content.…”
Section: Resultscontrasting
confidence: 57%
“…Omega-3 fatty acids have many beneficial effects on human health; e.g., they reduce the concentration of triacylglycerols in blood plasma, normalise blood pressure and have anticoagulant, antiatherosclerotic and anti-inflammatory and anticancer activity [55]. Shafey [56] reported that the age of laying hens had no effect on the concentration of palmitic (C16:0) or oleic (C18:1n9) acids. However, the content of stearic acid (C18:0) changed over the egg production period and was highest (P ≤ 0.05) in eggs from 31-week-old hens, and linoleic acid (C18:2n6) was highest in eggs from 51-week-old hens.…”
Section: Discussionmentioning
confidence: 99%